2018
DOI: 10.1016/j.ejmech.2017.11.069
|View full text |Cite
|
Sign up to set email alerts
|

A minimalistic approach to develop new anti-apicomplexa polyamines analogs

Abstract: The development of new chemical entities against the major diseases caused by parasites is highly desired. A library of thirty diamines analogs following a minimalist approach and supported by chemoinformatics tools have been prepared and evaluated against apicomplexan parasites. Different member of the series of N,N′−disubstituted aliphatic diamines shown in vitro activities at submicromolar concentrations and high levels of selectivity against Toxoplasma gondii and in chloroquine-sensitive and resistant-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…One of these is putrescine; previous studies have confirmed that it is a key component that allows the rapid growth of Babesia spp. and other Apicomplexa parasites [ 1 , 11 , 36 ]. This is further supported by in silico analysis of the B. bovis genome that has shown the parasite cannot biosynthesize polyamines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these is putrescine; previous studies have confirmed that it is a key component that allows the rapid growth of Babesia spp. and other Apicomplexa parasites [ 1 , 11 , 36 ]. This is further supported by in silico analysis of the B. bovis genome that has shown the parasite cannot biosynthesize polyamines [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phylum Apicomplexa comprises intracellular protozoan parasites of enormous global importance in the medical and veterinary fields [ 1 ]. Babesia bovis and B. bigemina are obligate intraerythrocytic parasites that cause bovine babesiosis in tropical and subtropical regions [ 2 , 3 ], and both parasites are transmitted by Rhipicephalus microplus or R. annulatus .…”
Section: Introductionmentioning
confidence: 99%
“…The standard antimalarial agent chloroquine and artemisinin were used as the positive controls and DMSO as negative control. 56,57…”
Section: Methodsmentioning
confidence: 99%
“…The standard antimalarial agent chloroquine and artemisinin were used as the positive controls and DMSO as negative control. 56,57 In vitro activity against L. donovani (IC 50 ). Leishmania donovani promastigotes of the S1 Sudan strain (2 × 10 6 cell per mL) were cultured at 26 °C in polystyrene cell-culture flasks (25 cm 2 ), containing RPMI-1640 medium (without sodium bicarbonate and sodium pyruvate) with 10% FBS.…”
Section: Biologymentioning
confidence: 99%
“…Hence, many scientists devoted part of their work to the analysis of protecting group strategies, as testified by the remarkable work done in late 1990s/early 2000s by Fukuyama and co-workers, [8][9][10][11][12] as well as by many others. [13][14][15][16][17][18][19][20][21][22][23] In the last years, our research group focused its efforts on the preparation of a series of compounds bearing interesting antifungal properties, as we reported in previous works, [24][25][26][27][28][29][30][31][32] well represented by compound 1 (Figure 1). These compounds showed good activities against various Candida strains, most notably albicans, guillermondii, kefyr, glabrata.…”
Section: Introductionmentioning
confidence: 99%